Potensi Antibakteri Beberapa Tumbuhan Obat Tradisional - Risa Nursanty; Zumaidar Zumaidar (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2010)
The research of antibacterial ability from Anacardium occidentale (Anacardiaceae), Lawsonia inermis (Lythraceae), Averrhoa bilimbi, Averrhoa carambola (Oxalidaceae), Capsicum frutescens and Solanum torvum (Solanaceae) to Escherichia coli ATCC 25922 and Staphylococcus  aureus ATCC 29213 was done from Mei until November 2010 at Microbiology laboratory, Natural Science, Syiah Kuala University. Leave and barks extracts of plant was soluted using n-Hexane solution. Antibacterial activities was tested by using diffusion method with each concentrations 10%, 20%, and 30%. The result showed that plants leaves and barks had ability to inhibit the growth of Staphylococcus  aureus ATCC 29213. The largest of inhibition zone was formed by L. inermis leaves extract in 6 mm. Meanwhile C. frutescens barks extract was showed inhibition zone in 5 mm.